2022
DOI: 10.1002/chem.202203006
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Ferrocene‐Based Diol Library and Application in the Hetero‐Diels‐Alder Reaction

Abstract: Diol scaffolds have been utilized as highly effective catalysts and ligands in a wide range of catalytic asymmetric transformations. For scaffolds to be successful as broadly used motifs, they should be prepared cheaply through facile routes and be easily handled. Herein, the synthesis of a family of planar chiral diols based on a modular and robust threestep route is described, which yields catalytically active diols in > 99 % de and > 99 % ee, with up to seven different chiral elements. These diols have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Unfortunately, these diols were not amenable to metal catalysis due to the steric bulk preventing coordination as a ligand. Further exploration of these diols through modification of the backbone failed to ameliorate this issue [31] . To circumvent this, we envisioned employing non‐C 2 symmetric systems, in which only one of the cyclopentadienyl rings is functionalized, as in 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, these diols were not amenable to metal catalysis due to the steric bulk preventing coordination as a ligand. Further exploration of these diols through modification of the backbone failed to ameliorate this issue [31] . To circumvent this, we envisioned employing non‐C 2 symmetric systems, in which only one of the cyclopentadienyl rings is functionalized, as in 5 .…”
Section: Resultsmentioning
confidence: 99%
“…We had previously reported the preparation of diols of the type 6 (Figure 1) and their application as hydrogen bond catalysts for the asymmetric HDA, achieving ees of up to 92 %. [28,31] Unfortunately, these diols were not amenable to metal catalysis due to the steric bulk preventing coordination as a ligand. Further exploration of these diols through modification of the backbone failed to ameliorate this issue.…”
Section: Ligand Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The stereoselectivity of the prepared ligands was maintained carefully and crystallographic data of such components were reported to confirm their structure. XRD study also revealed that these ligands exhibited both intricate inter-and intramolecular hydrogen bonding, along with uncommon, bifurcated hydrogen bonding interactions (Figure 27) [100].…”
Section: Applications Of Ferrocene-based Diols In Hetero Diels Alder ...mentioning
confidence: 99%
“…Within the broad field of palladium catalysis, allylic alkylation, also termed the Tsuji–Trost reaction, is a process that arguably offers the most versatility in terms of mechanistic possibilities and the ability to combine with other reaction types. It often affords chiral products, offering numerous possibilities for asymmetric synthesis through various mechanistic manifolds . A number of important classes of chiral ligands have been developed over the years, but it is important that new ligand exploration continues .…”
mentioning
confidence: 99%